Biosynthesis of menaquinone (vitamin K 2) and ubiquinone (coenzyme Q): A perspective on enzymatic mechanisms - Meganathan, R (Cofactor Biosynthesis: a Mechanistic Perspective, 2001)
The benzoquinone ubiquinone (coenzyme Q) and the naphthoquinones menaquinone (vitamin K 2) and demethylmenaquinone are derived from the shikimate pathway, which has been described as a “metabolic tree with many branches.” Menaquinone (MK) is considered a vitamin, but coenzyme (Q) is not; MK is an essential nutrient (it cannot be synthesized by mammals), whereas Q is not considered an essential nutrient since it can be synthesized from the amino acid tyrosine. The quinone nucleus of Q is derived directly from chorismate, whereas that of MK is derived from chorismate via isochorismate. The prenyl side chain of both quinones is derived from prenyl diphosphate, and the methyl groups are derived from S-adenosylmethionine. MK biosynthesis requires 2-ketoglutarate and the co-factors ATP, coenzyme A (CoASH), and thiamine pyrophosphate. In spite of the fact that both quinones originate from the shikimate pathway, there are important differences in their biosynthesis. In MK biosynthesis, the prenyl side chain is introduced in the next to last step, which is accompanied by loss of the carboxyl group, whereas in Q biosynthesis, the prenyl side chain is introduced at the second step, with retention of the carboxyl group. In MK biosynthesis, all the reactions of the pathway up to the prenylation (next to last step) are carried out by soluble enzymes, whereas all the enzymes involved in Q biosynthesis except the first are membrane bound. In MK biosynthesis the last step is a C-methylation; in Q biosynthesis, the last step is an O-methylation. In Q biosynthesis a second C-methylation and O-methylation take place in the middle part of the pathway. In spite of the fact that Q and MK biosynthesis diverges at chorismate, the C-methylations involved in both pathways are carried out by the same enzyme. Finally, Q biosynthesis under aerobic conditions requires molecular oxygen; anaerobic biosynthesis of Q and MK incorporates oxygen atoms derived from water. The current status of the pathways with particular emphasis on the reaction mechanisms, is discussed in this review.